INFLUENCE OF CEMENT GRADE ON STRENGTH PROPERTIES OF SANDCRETE BLOCKS - Nuruddeen, M. M.; Ma'aruf, A.; Murtala, S. A. (FUDMA Journal of Sciences, 2023)
This paper presents the result of experimental investigation to determine the influence of cement grade on compressive strength of hollow sandcrete blocks. 27 numbers of 225 x 225 x 450mm hollow sandcrete blocks were produced with three types of cement (Type 1 (grade 42.5), Type 2 (grade 32.5) and Type 3 (grade 32.5)) and were tested for density, compressive strength and water absorption. From the test results, the density of sandcrete blocks is higher in grade 42.5 than in grade 32.5. Also, the water absorption is lower in blocks with cement grade 42.5. Furthermore, the compressive strength is higher in sandcrete blocks with cement grade 42.5. It is concluded that higher cement grade improves the performance of hollow sandcrete blocks. It is therefore recommended that cement grade 42.5 should be used for sandcrete blocks production.